Diagnostic Nutrient Testing for Commercial Citrus in Florida - Rao Mylavarapu; Kelley Hines; Thomas Obreza (EDIS)
SL-279, a 6-page fact sheet by Rao Mylavarapu, Kelley Hines, and Thomas Obreza, presents the details of several types of diagnostic tests for nutrient status and management in commercial citrus groves in Florida, as well as sample submission procedures. Includes references and a copy of the sample submission form (in the pdf version). Published by the UF Soil and Water Science Department, December 2008.